EVALUATION OF FOLIAR SPRAY WITH EXTRACT OF MARINE ALGAE AND YEAST AND MOWING DATE ON GROWTH, YIELD, AND ACTIVE COMPONENTS OF WATERCRESS. - Zainab J. Al-Mousawi; Y. F. Salloom; Z.M. Abdul-Qader (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The experiment was implemented in the fields of the College of Agricultural Engineering Sciences / University of Baghdad during the agricultural season 2021-2022 as a factorial experiment (2 x 3 x 3) with within Randomized Complete Block Design using 3 replcates, The spraying with marine algae extract (0, 4, and 6ml.l-1) represented the first factor symbolized by K0, K1, and K2; the second factor involved spraying with the yeast extract (0, 2, and 4 mg.l-1) referred to as Y0, Y1, and Y2; while the third factor was mowing date as tow mows were applied with 15 days interval between them. The research was aimed to examine the effect of the three mentioned factors and their interaction on the vegetative growth and leaf biochemical traits of watercress plants. The research objectives Results showed a significant superiority of the interaction treatment Y2K2 in increasing number of leaves, leaf area, fresh weight, and dry weight in the second mow (62.80 leaves.plant-1, 131.77cm.plant-1, 265.30g, and 113.5g) as well as increasing the biochemical traits in leaves including the content of carbohydrates, protein, N, P, K, Glucosinolates, total Glucosinolates, total phenolic compounds, and total flavonoids in the second mow.